To determine the missing step in proving the equivalence of \( 12a+10+a=10+a+12a \) using the Commutative Property, we can rearrange the terms appropriately.
Let's break it down:
The goal is to express \( 12a + 10 + a \) in a way that highlights its equivalence to \( 10 + a + 12a \).
In Step 1, we can rearrange the terms:
Step 1: \( 10 + 12a + a = 10 + a + 12a \)
This matches the structure leading to Step 2. From Step 1, we can combine like terms (the \( 12a + a = 13a \)), giving us:
Step 2: \( 10 + 13a = 10 + 13a \)
Thus, the complete sequence is:
- Step 1: \( 10 + 12a + a = 10 + a + 12a \)
- Step 2: \( 10 + 13a = 10 + 13a \)
- Step 3: The expressions are equivalent because they both equal the same value.
Of the options provided, the correct missing step is:
10 + 12a + a = 10 + a + 12a.